Longitudinal analysis of body composition in Italian national U17 male handball players using bioelectrical impedance vector analysis - Serafini, S.; Papale, O.; di Credico, A.; Fusco, A.; Mascherini, G.; Izzicupo, P. (The Journal of Sports Medicine and Physical Fitness, 2026)
BACKGROUND: Monitoring body composition is crucial for optimizing performance and preventing injuries in young athletes during a competitive season. This study evaluated changes in body composition and bioelectrical impedance vector analysis (BIVA) in 15 male U17 Italian national handball players (age: 16.44±0.60 years).